2016
DOI: 10.2334/josnusd.58.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type 2 diabetes mellitus and smoking on periodontal parameters and salivary matrix metalloproteinase-8 levels

Abstract: The present study was carried out to evaluate the effect of type 2 diabetes mellitus (DM) and smoking on periodontal parameters and on the levels of salivary matrix metalloproteinase (MMP-8). One hundred and twenty five subjects were divided into five groups: group 1, systemically and periodontally healthy subjects (n = 25); group 2, systemically healthy subjects but with chronic periodontitis (n = 25); group 3, subjects with type 2 DM and chronic periodontitis (n = 25); group 4, smokers with chronic periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…How this effect is realized goes beyond the scope of this study, but it is safe to assume that the process has both microvascular and immunological components, and it is probably the meeting of these different pathogenic pathways that gives rise to the observed massive deterioration. Some studies have addressed the issue of the effect of smoking and DM on periodontal health [ 50 52 ], but none of these concentrated explicitly on the interaction of the two factors. Our results are new in this respect and demonstrate another way in which smoking can do further damage to the health of patients with DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How this effect is realized goes beyond the scope of this study, but it is safe to assume that the process has both microvascular and immunological components, and it is probably the meeting of these different pathogenic pathways that gives rise to the observed massive deterioration. Some studies have addressed the issue of the effect of smoking and DM on periodontal health [ 50 52 ], but none of these concentrated explicitly on the interaction of the two factors. Our results are new in this respect and demonstrate another way in which smoking can do further damage to the health of patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious weakness of that study was that only patients with PD were enrolled in the study and, consequently, no comparison was made with healthy controls [ 49 ]. Gupta and colleagues investigated the relationship between T2D and smoking in patients with PD and observed that the periodontal status of these patients with PD was significantly worse in the group of smokers with DM than in the group of non-smokers with T2D [ 50 ]. Obrak and co-workers found that the periodontal status of non-smokers with T2D with and PD was better than that of their smoking counterparts [ 51 ], while Javed and co-workers found that both DM and smoking had a detrimental effect on the periodontal status of patients [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…35 Uncontrolled diabetes influences the expression of tissue-degrading enzymes in the inflamed gingiva, leading to up-regulation of the ratio between metalloproteinase and their inhibitors. 36,37 A two-way association or interaction between diabetes and periodontitis has been postulated, assuming that either condition interferes with the other. A somewhat different view may postulate the interaction as a type of vicious circle, as exemplified in Figure 2.…”
Section: Diabetes-periodontitis Interactionmentioning
confidence: 99%
“…Additionally, immune response is modified and the pathogenesis of the disease is negatively affected [8]. A similar pattern is present in patients affected by type 2 diabetes mellitus suggesting that diabetic-smoker patients have increased periodontal breakdown and are prone to a more severe periodontitis [9].…”
Section: Comprehensive Diagnosismentioning
confidence: 49%